Early Noninvasive Monitoring of Hypoxic State of Diabetic Foot Based on Diffuse Reflectance Spectroscopy - Xu, Ge; Dong, Liquan; Yuan, Jing; Zhao, Yuejin; Liu, Ming; Hui, Mei; Kong, Lingqin (Frontiers in Physics, 2022)
Early accurate diagnosis and assessment severity of the hypoxic state of diabetic foot is of paramount importance. In this paper, a noninvasive monitoring method of the hypoxic state of the diabetic foot based on diffuse reflectance spectroscopy is proposed. Monte Carlo simulation method is used to imitate the effect on diffuse reflectance of the foot from different blood volume fractions and blood oxygen saturations. Moreover, the in vivo experiments of the hypoxic state of the foot based on the binding method is carried out using an integrating sphere system. Monte Carlo simulation results show that the diffuse reflectance of the foot under normal state and hypoxic state is significantly different. In vivo experimental results are highly consistent with the Monte Carlo simulation results. In vivo experiments further indicate that 6 characteristic wavelengths (440nm, 469nm, 514nm, 540nm, 560nm, and 576nm) of the diffuse reflectance are more able to distinguish the normal oxygen state and hypoxic states of the foot. The proposed method promotes the development and application of the diffuse reflectance spectroscopy method in the noninvasive detection of biological tissue.